2012
DOI: 10.1002/ps.3450
|View full text |Cite
|
Sign up to set email alerts
|

Target‐site mutation associated with cross‐resistance to ALS‐inhibiting herbicides in late watergrass (Echinochloa oryzicola Vasing.)

Abstract: This is the first report of Echinochloa oryzicola cross-resistance to ALS-inhibiting herbicides as a result of Trp574Leu mutation. The cpDNA sequence comparison analysis is a reliable tool for discrimination of conventionally classified E. crus-galli and E. oryzicola accessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 28 publications
1
46
1
2
Order By: Relevance
“…For example, Ala122 or Ser653 substitution results in resistance to IMIs but not to SUs, whereas Pro197 substitution usually results in resistance to SUs but not IMIs. Substitution of Trp574 bestows high resistance levels to all ALS inhibitors [22][23][24][25]. Based on the results of this study, resistance to three classes of ALS-inhibiting herbicides was confirmed in A. aequalis.…”
Section: Discussionmentioning
confidence: 55%
“…For example, Ala122 or Ser653 substitution results in resistance to IMIs but not to SUs, whereas Pro197 substitution usually results in resistance to SUs but not IMIs. Substitution of Trp574 bestows high resistance levels to all ALS inhibitors [22][23][24][25]. Based on the results of this study, resistance to three classes of ALS-inhibiting herbicides was confirmed in A. aequalis.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, there has been speculation that hybridization occurs between the three species (Th ebaud and Abbott, 1995), but this hypothesis remains up to now unconfirmed. This indicates that molecular techniques are needed which are reliable to study the evolutionary history and species divergence of plants, as well as for solving taxonomic confusion between species (Clegg and Zurawski, 1992;Kaloumenos et al, 2013). More specifically, a chloroplast DNA (cpDNA) with a slow evolution rate and no recombination owing to the maternal inheritance of the organelle genome has been useful in examining relationships among different plant species (Clegg and Zurawski, 1992;Wolfe et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…crus-galli demonstrated resistance to cyhalofop-butyl and were also confirmed to be cross-resistant to other ACCase inhibiting herbicides, fenoxaprop-p-ethyl and metamifop ). Kaloumenos et al (2013) reported that Echinochloa oryzicola accessions were found to be cross-resistant to penoxsulam, bispyribac-sodium, imazamox, foramusulfuron, nicisulfuron and rimsulfuron. E. oryzicola cross-resistance to ALSherbicides was due to the result of Trp574Leu mutation.…”
mentioning
confidence: 99%